Myths of Masculine Identity and Local Traditions in Wadimor Sarong Advertisements: A Semiotic Analysis Based on Roland Barthes - Febriani Nirmawati Siagian; Yesica Angel Damanik; Veni Nadia; Sri Indah Ayu; Tengku Ratna Soraya; Fitri Ervina Tarigan (Raja Zulkarnain Education Foundation, 2026)
Studies on the construction of masculine identity myths rooted in local tradition within Indonesian cultural product advertisements remain searce. This study aims to analyze the construction of masculine identity myths and the representation of local tradition in the 2021 Sarung Wadimor advertisement using Roland Barthes’ three-level semiotic framework denotation, connotation, and myth. A descriptive qualitative method waz employed through textual observation and documentation of six advertisement scenes as units of analysis. The findings reveal three systematically operating myths: (1) a tradition-based masculinity myth that naturalizes the ideal Indonesian man as one deeply rooted in cultural heritage, (2) a religious masculinity myth that positions spiritual piety as a mandatory public component of Muslim masculine identity, and (3) a social nationalist masculinity myth that interpellates Indonesian men to percerve the choice of local products as a declaration of national pride. These three myths form a coherent ideological system through Barthes’ naturalization mechanism, transforming sarung from a mere textile product into an active medium for constructing masculine identity. This research demonstrates that advertisements not only promote products but also shape society’s perceptions of masculine identity, expanding the study of masculinity in Indonesian advertising by incorporating cultural and religious perspectives